SEJARAH PENDIDIKAN KRISTEN DAN PERKEMBANGAN KEMATANGAN PAK GEREJA: PERJALANAN PANJANG DAN TANTANGAN - Ruth Anna Marietta Sianturi; Maniar Arnida Samosir (Sekolah Tinggi Teologi Bethel The Way Jakarta, 2023)
This article discusses the history of the development of Christian education towards the maturity of Church Christian Education. The research method used is a literature study, by collecting and analyzing various sources related to this topic. In this article will outline the development of Christian education from the early period to the present, as well as the definition and importance of the maturity of Christian Education. Furthermore, this article discusses the role of Christian education in achieving the maturity of Christian Education, including the formation of Christian character, correct understanding of the Bible, and the development of mature Christian theology. The challenges faced in achieving the maturity of Christian education are also discussed in this article, both internally and externally from the church. This article is expected to provide a deeper understanding of the history of the development of Christian education and the importance of achieving the maturity of Christian education, as well as providing recommendations for the future.